Teknologi MEB sebagai Solusi Pengelolaan Sampah Organik Menuju Desa Mandiri di Kabupaten Sukabumi - Alphanoda, Abid Fahreza; Kurniawan, Yani; Rahayu, Dyah Sulistyowati; Ningsih, Ratih Hendra; Shidiq, Muhammad Hafizh (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Mangkalaya Village in Sukabumi Regency faces the problem of organic waste management that has not been optimally handled. Approximately 115.10 m³ of waste per month with a composition of 56% organic waste, only 36% is transported to the landfill, while the rest is burned or dumped into the environment, causing pollution, health risks, and greenhouse gas emissions. This community service activity aims to implement Microbial Electrolysis Biodigester (MEB) Technology as a solution for processing organic waste into biogas and liquid organic fertilizer, while empowering the community to become an independent village in processing waste. The approach used includes socialization, technical and business management training, construction and commissioning of a community-scale MEB reactor unit, operational assistance, and technology and socio-economic evaluation. Data were collected through field observations, interviews, reactor operational records, and documentation of the activities of ABEL Porridge and Wet Cake MSME partners. The program successfully installed one MEB reactor unit with a design capacity of 1,000 L of organic waste, to process household waste and remaining MSME raw materials. Initial operational tests showed that the reactor was able to produce biogas that began to be used on a household scale and liquid organic fertilizer that was tested on residents' land. Waste incineration practices have decreased, while organic waste sorting has increased in partner households. However, through intensive mentoring and strengthening the role of partners, most of the first-year output indicators, including technology installation, increased production capacity, the formation of management groups, and publications, have been achieved. The implementation of MEB in Mangkalaya Village has proven technically and socially feasible as the first step for an independent village to manage waste. The next phase focuses on optimizing operations, strengthening the biogas and fertilizer business model, and replication to other villages.ABSTRAKDesa Mangkalaya di Kabupaten Sukabumi menghadapi persoalan pengelolaan sampah organik yang belum tertangani optimal. Sekitar 115,10 m³ sampah per bulan dengan komposisi 56% sampah organik hanya 36% yang terangkut ke TPA, sedangkan sisanya dibakar atau dibuang ke lingkungan sehingga menimbulkan pencemaran, risiko kesehatan, dan emisi gas rumah kaca. Kegiatan pengabdian ini bertujuan menerapkan Teknologi Mikroba Elektrolisis Biodigester (MEB) sebagai solusi pengolahan sampah organik menjadi biogas dan pupuk organik cair, sekaligus memberdayakan masyarakat menuju desa mandiri mengolah sampah. Pendekatan yang digunakan meliputi sosialisasi, pelatihan teknis dan manajemen usaha, pembangunan dan komisioning satu unit reaktor MEB skala komunitas, pendampingan operasional, serta evaluasi teknologi dan sosial-ekonomi. Data dikumpulkan melalui observasi lapangan, wawancara, pencatatan operasional reaktor, dan dokumentasi aktivitas mitra UMKM Bubur dan Kue Basah ABEL. Program berhasil memasang satu unit reaktor MEB berkapasitas desain 1.000 L sampah organik, untuk mengolah sampah rumah tangga dan sisa bahan baku UMKM. Uji operasi awal menunjukkan reaktor mampu menghasilkan biogas yang mulai dimanfaatkan pada skala rumah tangga serta pupuk organik cair yang diuji pada lahan warga. Praktik pembakaran sampah berkurang, sementara pemilahan sampah organik di rumah tangga mitra mulai meningkat. Namun, melalui pendampingan intensif dan penguatan peran mitra, sebagian besar indikator luaran tahun pertama yaitu instalasi teknologi, peningkatan kapasitas produksi, terbentuknya kelompok pengelola, serta publikasi dapat dicapai. Penerapan MEB di Desa Mangkalaya terbukti layak secara teknis dan sosial sebagai langkah awal desa mandiri mengolah sampah. Tahapan berikutnya difokuskan pada optimasi operasi, penguatan model bisnis biogas dan pupuk, serta replikasi ke desa lain.